Perception and Practice of Assessment for Learning: A Case from Tribhuvan University Faculty of Management - Acharya, Devi R.; Poudel, Lekha N. (Molung Educational Frontier, 2025)
Assessment for learning plays a crucial role in enhancing student learning by integrating student assessment into the teaching-learning process. Taking a case from Tribhuvan University, we conducted a study on the practice of assessment for learning in higher education in Nepal. In this study, we analyzed the perceptions and practices of teaching faculty regarding assessment for learning. The primary research question focused on faculty members’ perceptions and practices related to assessment for learning and how these practices contribute to student learning. We employed both quantitative (an online survey) and qualitative (in-depth interviews) methods for data collection. This study utilized descriptive analysis for the quantitative data, supplemented by qualitative analysis of the interviews. Our findings revealed that faculty members have a limited understanding of assessment for learning, and their practices are inadequate in this regard. To enhance the overall quality of higher education, there is a need to improve student assessment practices by adopting assessment for learning. This requires changes in assessment policies, enhancement of faculty capacities, and improvement in institutional environment.